Zora! : the life of Zora Neale Hurston - Fradin, Judith Bloom; Fradin, Dennis B. (Houghton Mifflin Harcourt, 2019)
Presents a biography of Zora Neale Hurston, chronicling her childhood and detailing the influences that shaped her career as an author. Examines how Hurston worked through the poverty that followed her much of her life and charts the rise in the popularity of her books that followed her death. Includes black-and-white photographs.